Behavioural welfare analysis and revealed preference: Theory and experimental evidence - Daniele Caliari (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Behavioural welfare economics provides tools to elicit welfare preferences when individuals use nonstandard behavioural models. Current proposals either require assumptions on the models or elicit preferences that become coarser and coarser as the dataset grows. We propose an informational property [Informational Responsiveness] that solves the coarseness problem and, as the dataset grows, characterizes the family of welfare preference elicitation tools that elicit the underlying utility function of a broad family of stochastic models, denoted as preference monotonic models. As such, we argue that Informational Responsiveness is an important property of preference elicitation tools. We then test our property in an experiment in which participants first face a sequence of questions regarding time and risk outcomes and second report their preferences over a subset of the alternatives. We find that preference elicitation tools that satisfy our requirement provide a significantly better match between the elicited and the reported welfare relation.
Keywords: D0; D6; 330; Behavioural Welfare economics; Bounded rationality; Stochastic choice; Revealed preference